The Moderating Effect of Gender Differences between Mentoring and Individuals’ Career - Ismail, Azman; Ibrahim, Zalina; Jusoff, Kamaruzaman; Kho, Michael Khian Jui; Jaya, Irdawaty; Mahdi, Ahmad Faisal (2009)
This study was conducted to examine the effect of mentoring program and gender differences on individuals’ career using 153 usable questionnaires gathered from employees who work in one public university in Sarawak, Malaysia. Outcomes of hierarchical regression analysis showed two important findings: firstly, interaction between formal mentoring and gender differences positively and significantly correlated with individuals’ career. Secondly, interaction between informal mentoring and gender differences positively and significantly correlated with individuals’ career. This result confirms that gender differences do act as a moderating variable in the mentoring model of the organizational sample. In addition, implications and discussion are elaborated.